2022
DOI: 10.3390/nu14122457
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Diet Quality, Advice, and Dietary Interventions in Individuals with Diabetes-Related Foot Ulceration; A Qualitative Research Study

Abstract: Background: Dietary intake is a recognised contributor to healing in diabetes-related foot ulceration (DFU). However, it is currently unknown how individuals with DFU perceive their diet, and what is deemed an acceptable dietary intervention. Therefore, the aims of this study were to explore perceptions of diet quality, previous dietary advice, and dietary interventions in individuals with DFU, and secondly to determine acceptable dietary interventions in individuals with DFU to assist with wound healing. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…A potential contributing factor to the lack of confidence in nutrition assessment by doctors may relate to a lack of easily applied screening tools that are suited to medical and other health practitioners. An additional major barrier to referring individuals with DFU for nutritional support for wound healing was the patient perception of dietitians as judgemental, aligning with previous research exploring the perceptions of individuals with DFU 60 . There is a need to overcome the negative stereotype of dietitians as authoritarian figures, but rather as enablers of behaviour change and leaders in positive dietary behaviours.…”
Section: Discussionmentioning
confidence: 61%
See 4 more Smart Citations
“…A potential contributing factor to the lack of confidence in nutrition assessment by doctors may relate to a lack of easily applied screening tools that are suited to medical and other health practitioners. An additional major barrier to referring individuals with DFU for nutritional support for wound healing was the patient perception of dietitians as judgemental, aligning with previous research exploring the perceptions of individuals with DFU 60 . There is a need to overcome the negative stereotype of dietitians as authoritarian figures, but rather as enablers of behaviour change and leaders in positive dietary behaviours.…”
Section: Discussionmentioning
confidence: 61%
“…Furthermore, advice and management should be based on an objective nutrition assessment, which is imperative to providing personalised medical nutrition therapy 59 . Previous research concluded individuals with DFU are seeking personalised dietetic support that considers their capabilities, opportunities and motivations 60 . A potential contributing factor to the lack of confidence in nutrition assessment by doctors may relate to a lack of easily applied screening tools that are suited to medical and other health practitioners.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations